The Special Power of the State Attorney General in Preventing Governmental Product/Service Procurement-Related Crime in Indonesia - Fahmi, Fahmi; Zaidun, Moch; Suheryadi, Bambang (Yuridika, 2021)
The basic duty of the Republic of Indonesia's General Attorney in the Special Crime Division is to undertake a repressive function. A preventive strategy includes actions taken to prevent product/service corruption crime by the Civil and State Administration Division of Indonesia's Attorney General (DATUN). This study aims to analyse the construction of JPN authorisation based on Indonesia's Attorney General Law. The method used in this study was a juridical, normative one. The results show that given the textual meaning with a grammatical interpretation related to the attorney's duty and authority in civil and state administration based on Article 30, Clause (2) of Indonesia's Attorney General Law in terms of acting for and on behalf of the state or government, the prosecutor in the civil and state administration area should have special power. The clause emphasises the phrase "special power” but does not mention explicitly the State Attorney General. Nevertheless, the interpretation of special power as mentioned in Article 30, Clause (2) of the Attorney General Law to be State General Attorney is found in the Republic of Indonesia Attorney General's Regulation. However, in the concept of norm constructed, this authority should be preceded by a demand. The translation of JPN in the context of function provides a legal deliberation where, on the one hand, the absence of special power of attorney facilitates the role of JPN in attempting to prevent corruption crime, but on the other hand, causes an inconsistent application of the rule.